Enhanced A3 adenosine receptor selectivity of multivalent nucleoside-dendrimer conjugates - Shainberg Asher; Lloyd John; Gao Zhan-Guo; Klutz Athena M; Jacobson Kenneth A (Journal of Nanobiotechnology, 2008)
Abstract Background An approach to use multivalent dendrimer carriers for delivery of nucleoside signaling molecules to their cell surface G protein-coupled receptors (GPCRs) was recently introduced. Results A known adenosine receptor (AR) agonist was conjugated to polyamidoamine (PAMAM) dendrimer carriers for delivery of the intact covalent conjugate to on the cell surface. Depending on the linking moiety, multivalent conjugates of the N6-chain elongated functionalized congener ADAC (N6-[4-[[[4-[[[(2-aminoethyl)amino]carbonyl]methyl]anilino]carbonyl]methyl]phenyl]-adenosine) achieved unanticipated high selectivity in binding to the cytoprotective human A3 AR, a class A GPCR. The key to this selectivity of > 100-fold in both radioreceptor binding (Ki app = 2.4 nM) and functional assays (EC50 = 1.6 nM in inhibition of adenylate cyclase) was maintaining a free amino group (secondary) in an amide-linked chain. Attachment of neutral amide-linked chains or thiourea-containing chains preserved the moderate affinity and efficacy at the A1 AR subtype, but there was no selectivity for the A3 AR. Since residual amino groups on dendrimers are associated with cytotoxicity, the unreacted terminal positions of this A3 AR-selective G2.5 dendrimer were present as carboxylate groups, which had the further benefit of increasing water-solubility. The A3 AR selective G2.5 dendrimer was also visualized binding the membrane of cells expressing the A3 receptor but did not bind cells that did not express the receptor. Conclusion This is the first example showing that it is feasible to modulate and even enhance the pharmacological profile of a ligand of a GPCR based on conjugation to a nanocarrier and the precise structure of the linking group, which was designed to interact with distal extracellular regions of the 7 transmembrane-spanning receptor. This ligand tool can now be used in pharmacological models of tissue rescue from ischemia and to probe the existence of A3 AR dimers.